Generation Z on the Choice of Religious Authorities: A Case Study of Religious Communities in Yogyakarta - Haira Rizka (UIN Raden Mas Said Surakarta, 2019)
The Internet emergence among generation Z in Yogyakarta portrays a unique phenomenon in selecting religious preachers. This research investigates how generation Z perceives religious authority. The formulation is answered by Carette’s psychological-religious experience theory. This is a descriptive qualitative research describing the phenomenon of generation Z in perceiving religious authorities. The objects were 15 respondents from 6 religious communities in Yogyakarta. The data were collected through questionnaire and interviews to gain in depth analysis and analyzed through collective case study. The research reveals: first, those who utilize internet as their main resource put more belief on new preachers such as Abdul Somad, Felix Xiaw, etc. and believe that traditional kyais hold less Islamic spirit; and second, those who utilize internet as their additional resource respect more traditional kyais such as Mustofa Bisri, Buya Syafii Maarif, etc. who emphasize on Islam Nusantara, and consider that new preachers hold rigid Islamic values.